If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (n + -6)(n + -1)(n + -2)(n + -3)(n + -4)(n + -5) = 0 Reorder the terms: (-6 + n)(n + -1)(n + -2)(n + -3)(n + -4)(n + -5) = 0 Reorder the terms: (-6 + n)(-1 + n)(n + -2)(n + -3)(n + -4)(n + -5) = 0 Reorder the terms: (-6 + n)(-1 + n)(-2 + n)(n + -3)(n + -4)(n + -5) = 0 Reorder the terms: (-6 + n)(-1 + n)(-2 + n)(-3 + n)(n + -4)(n + -5) = 0 Reorder the terms: (-6 + n)(-1 + n)(-2 + n)(-3 + n)(-4 + n)(n + -5) = 0 Reorder the terms: (-6 + n)(-1 + n)(-2 + n)(-3 + n)(-4 + n)(-5 + n) = 0 Multiply (-6 + n) * (-1 + n) (-6(-1 + n) + n(-1 + n))(-2 + n)(-3 + n)(-4 + n)(-5 + n) = 0 ((-1 * -6 + n * -6) + n(-1 + n))(-2 + n)(-3 + n)(-4 + n)(-5 + n) = 0 ((6 + -6n) + n(-1 + n))(-2 + n)(-3 + n)(-4 + n)(-5 + n) = 0 (6 + -6n + (-1 * n + n * n))(-2 + n)(-3 + n)(-4 + n)(-5 + n) = 0 (6 + -6n + (-1n + n2))(-2 + n)(-3 + n)(-4 + n)(-5 + n) = 0 Combine like terms: -6n + -1n = -7n (6 + -7n + n2)(-2 + n)(-3 + n)(-4 + n)(-5 + n) = 0 Multiply (6 + -7n + n2) * (-2 + n) (6(-2 + n) + -7n * (-2 + n) + n2(-2 + n))(-3 + n)(-4 + n)(-5 + n) = 0 ((-2 * 6 + n * 6) + -7n * (-2 + n) + n2(-2 + n))(-3 + n)(-4 + n)(-5 + n) = 0 ((-12 + 6n) + -7n * (-2 + n) + n2(-2 + n))(-3 + n)(-4 + n)(-5 + n) = 0 (-12 + 6n + (-2 * -7n + n * -7n) + n2(-2 + n))(-3 + n)(-4 + n)(-5 + n) = 0 (-12 + 6n + (14n + -7n2) + n2(-2 + n))(-3 + n)(-4 + n)(-5 + n) = 0 (-12 + 6n + 14n + -7n2 + (-2 * n2 + n * n2))(-3 + n)(-4 + n)(-5 + n) = 0 (-12 + 6n + 14n + -7n2 + (-2n2 + n3))(-3 + n)(-4 + n)(-5 + n) = 0 Combine like terms: 6n + 14n = 20n (-12 + 20n + -7n2 + -2n2 + n3)(-3 + n)(-4 + n)(-5 + n) = 0 Combine like terms: -7n2 + -2n2 = -9n2 (-12 + 20n + -9n2 + n3)(-3 + n)(-4 + n)(-5 + n) = 0 Multiply (-12 + 20n + -9n2 + n3) * (-3 + n) (-12(-3 + n) + 20n * (-3 + n) + -9n2 * (-3 + n) + n3(-3 + n))(-4 + n)(-5 + n) = 0 ((-3 * -12 + n * -12) + 20n * (-3 + n) + -9n2 * (-3 + n) + n3(-3 + n))(-4 + n)(-5 + n) = 0 ((36 + -12n) + 20n * (-3 + n) + -9n2 * (-3 + n) + n3(-3 + n))(-4 + n)(-5 + n) = 0 (36 + -12n + (-3 * 20n + n * 20n) + -9n2 * (-3 + n) + n3(-3 + n))(-4 + n)(-5 + n) = 0 (36 + -12n + (-60n + 20n2) + -9n2 * (-3 + n) + n3(-3 + n))(-4 + n)(-5 + n) = 0 (36 + -12n + -60n + 20n2 + (-3 * -9n2 + n * -9n2) + n3(-3 + n))(-4 + n)(-5 + n) = 0 (36 + -12n + -60n + 20n2 + (27n2 + -9n3) + n3(-3 + n))(-4 + n)(-5 + n) = 0 (36 + -12n + -60n + 20n2 + 27n2 + -9n3 + (-3 * n3 + n * n3))(-4 + n)(-5 + n) = 0 (36 + -12n + -60n + 20n2 + 27n2 + -9n3 + (-3n3 + n4))(-4 + n)(-5 + n) = 0 Combine like terms: -12n + -60n = -72n (36 + -72n + 20n2 + 27n2 + -9n3 + -3n3 + n4)(-4 + n)(-5 + n) = 0 Combine like terms: 20n2 + 27n2 = 47n2 (36 + -72n + 47n2 + -9n3 + -3n3 + n4)(-4 + n)(-5 + n) = 0 Combine like terms: -9n3 + -3n3 = -12n3 (36 + -72n + 47n2 + -12n3 + n4)(-4 + n)(-5 + n) = 0 Multiply (36 + -72n + 47n2 + -12n3 + n4) * (-4 + n) (36(-4 + n) + -72n * (-4 + n) + 47n2 * (-4 + n) + -12n3 * (-4 + n) + n4(-4 + n))(-5 + n) = 0 ((-4 * 36 + n * 36) + -72n * (-4 + n) + 47n2 * (-4 + n) + -12n3 * (-4 + n) + n4(-4 + n))(-5 + n) = 0 ((-144 + 36n) + -72n * (-4 + n) + 47n2 * (-4 + n) + -12n3 * (-4 + n) + n4(-4 + n))(-5 + n) = 0 (-144 + 36n + (-4 * -72n + n * -72n) + 47n2 * (-4 + n) + -12n3 * (-4 + n) + n4(-4 + n))(-5 + n) = 0 (-144 + 36n + (288n + -72n2) + 47n2 * (-4 + n) + -12n3 * (-4 + n) + n4(-4 + n))(-5 + n) = 0 (-144 + 36n + 288n + -72n2 + (-4 * 47n2 + n * 47n2) + -12n3 * (-4 + n) + n4(-4 + n))(-5 + n) = 0 (-144 + 36n + 288n + -72n2 + (-188n2 + 47n3) + -12n3 * (-4 + n) + n4(-4 + n))(-5 + n) = 0 (-144 + 36n + 288n + -72n2 + -188n2 + 47n3 + (-4 * -12n3 + n * -12n3) + n4(-4 + n))(-5 + n) = 0 (-144 + 36n + 288n + -72n2 + -188n2 + 47n3 + (48n3 + -12n4) + n4(-4 + n))(-5 + n) = 0 (-144 + 36n + 288n + -72n2 + -188n2 + 47n3 + 48n3 + -12n4 + (-4 * n4 + n * n4))(-5 + n) = 0 (-144 + 36n + 288n + -72n2 + -188n2 + 47n3 + 48n3 + -12n4 + (-4n4 + n5))(-5 + n) = 0 Combine like terms: 36n + 288n = 324n (-144 + 324n + -72n2 + -188n2 + 47n3 + 48n3 + -12n4 + -4n4 + n5)(-5 + n) = 0 Combine like terms: -72n2 + -188n2 = -260n2 (-144 + 324n + -260n2 + 47n3 + 48n3 + -12n4 + -4n4 + n5)(-5 + n) = 0 Combine like terms: 47n3 + 48n3 = 95n3 (-144 + 324n + -260n2 + 95n3 + -12n4 + -4n4 + n5)(-5 + n) = 0 Combine like terms: -12n4 + -4n4 = -16n4 (-144 + 324n + -260n2 + 95n3 + -16n4 + n5)(-5 + n) = 0 Multiply (-144 + 324n + -260n2 + 95n3 + -16n4 + n5) * (-5 + n) (-144(-5 + n) + 324n * (-5 + n) + -260n2 * (-5 + n) + 95n3 * (-5 + n) + -16n4 * (-5 + n) + n5(-5 + n)) = 0 ((-5 * -144 + n * -144) + 324n * (-5 + n) + -260n2 * (-5 + n) + 95n3 * (-5 + n) + -16n4 * (-5 + n) + n5(-5 + n)) = 0 ((720 + -144n) + 324n * (-5 + n) + -260n2 * (-5 + n) + 95n3 * (-5 + n) + -16n4 * (-5 + n) + n5(-5 + n)) = 0 (720 + -144n + (-5 * 324n + n * 324n) + -260n2 * (-5 + n) + 95n3 * (-5 + n) + -16n4 * (-5 + n) + n5(-5 + n)) = 0 (720 + -144n + (-1620n + 324n2) + -260n2 * (-5 + n) + 95n3 * (-5 + n) + -16n4 * (-5 + n) + n5(-5 + n)) = 0 (720 + -144n + -1620n + 324n2 + (-5 * -260n2 + n * -260n2) + 95n3 * (-5 + n) + -16n4 * (-5 + n) + n5(-5 + n)) = 0 (720 + -144n + -1620n + 324n2 + (1300n2 + -260n3) + 95n3 * (-5 + n) + -16n4 * (-5 + n) + n5(-5 + n)) = 0 (720 + -144n + -1620n + 324n2 + 1300n2 + -260n3 + (-5 * 95n3 + n * 95n3) + -16n4 * (-5 + n) + n5(-5 + n)) = 0 (720 + -144n + -1620n + 324n2 + 1300n2 + -260n3 + (-475n3 + 95n4) + -16n4 * (-5 + n) + n5(-5 + n)) = 0 (720 + -144n + -1620n + 324n2 + 1300n2 + -260n3 + -475n3 + 95n4 + (-5 * -16n4 + n * -16n4) + n5(-5 + n)) = 0 (720 + -144n + -1620n + 324n2 + 1300n2 + -260n3 + -475n3 + 95n4 + (80n4 + -16n5) + n5(-5 + n)) = 0 (720 + -144n + -1620n + 324n2 + 1300n2 + -260n3 + -475n3 + 95n4 + 80n4 + -16n5 + (-5 * n5 + n * n5)) = 0 (720 + -144n + -1620n + 324n2 + 1300n2 + -260n3 + -475n3 + 95n4 + 80n4 + -16n5 + (-5n5 + n6)) = 0 Combine like terms: -144n + -1620n = -1764n (720 + -1764n + 324n2 + 1300n2 + -260n3 + -475n3 + 95n4 + 80n4 + -16n5 + -5n5 + n6) = 0 Combine like terms: 324n2 + 1300n2 = 1624n2 (720 + -1764n + 1624n2 + -260n3 + -475n3 + 95n4 + 80n4 + -16n5 + -5n5 + n6) = 0 Combine like terms: -260n3 + -475n3 = -735n3 (720 + -1764n + 1624n2 + -735n3 + 95n4 + 80n4 + -16n5 + -5n5 + n6) = 0 Combine like terms: 95n4 + 80n4 = 175n4 (720 + -1764n + 1624n2 + -735n3 + 175n4 + -16n5 + -5n5 + n6) = 0 Combine like terms: -16n5 + -5n5 = -21n5 (720 + -1764n + 1624n2 + -735n3 + 175n4 + -21n5 + n6) = 0 Solving 720 + -1764n + 1624n2 + -735n3 + 175n4 + -21n5 + n6 = 0 Solving for variable 'n'. The solution to this equation could not be determined.
| 5=3(3-2x)+4(6-2x) | | (2+n)(n-1)(n-2)(n-3)(n-4)(n-5)=0 | | 6a^2x^2-abx-5b^2=0 | | 3x-12-1(x+4)=0 | | 10y-3=7y+9 | | 14+3n=20 | | 2(y-2)+5(2-y)=-3y(2y+2) | | 4*2x+1+5*2x+1=200*x | | x^4=2x^2+63 | | x^2-10x=-1025 | | x(x+4)(2x+5)=0 | | 7x+20=72 | | 4(2x-5)=5+4 | | a=5(x+8) | | xx+2x+7=7 | | A-40=5x | | 5X*3+3X=13 | | a=5x+40 | | 1.7+5(2.1x+0.4)=2 | | 6x+4y=95 | | 7x+20=56 | | 8=x+8.4-1.2x | | 8y+13= | | 8(y-3)-3=56 | | 28y+5=49 | | 28y+5=27 | | 2x+167=11x-13 | | 7m-11=59 | | 9h+6=87 | | 7m+3=59 | | sin(2x+5)=sin(x-1) | | x^3-6x^2+20x=0 |